Strong interference effects in the resonant Auger decay of atoms induced by intense x-ray fields - Demekhin, Philipp V.; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2011)
The theory of resonant Auger decay of atoms in a high-intensity coherent x-ray pulse is presented. The theory includes the coupling between the ground state and the resonance due to an intense x-ray pulse, taking into account the decay of the resonance and the direct photoionization of the ground state, both populating the final ionic states coherently. The theory also considers the impact of the direct photoionization of the resonance state itself which typically populates highly excited ionic states. The combined action of the resonant decay and of the direct ionization of the ground state in the field induces a non-Hermitian time-dependent coupling between the ground and the “dressed” resonance stats. The impact of these competing processes on the total electron yield and on the 2s22p4(1D)3p 2P spectator and 2s12p6 2S participator Auger decay spectra of the Ne 1s→3p resonance is investigated. The role of the direct photoionization of the ground state and of the resonance increases dramatically with the field intensity. This results in strong interference effects with distinct patterns in the electron spectra, which differ for the participator and spectator final states.
Gesehen am 05.05.2022